(untitled) (Journal of Medicine, 2022)
Introduction: Osteoporosis is a silent disaster among postmenopausal women worldwide and carries the highest contribution to morbidity and mortality, especially with concomitant Diabetes Mellitus. Materials and Methods: This was a cross-sectional observational study conducted to evaluate Osteoporosis in postmenopausal women having diabetes mellitus attending outdoor in the department of Physical Medicine & Rehabilitation, BSMMU. The study was conducted from July 2020 to June 2021. A total of 54 patients were included in the study. Results: Osteoporosis of the lumbar spine and femoral neck were present among 72.2% and 55.6% of respondents. Osteoporosis of at least one site was present among 83.3% of respondents. Statistically, a significant relationship was found between osteoporosis and co morbidity, BMI, age of onset of menstruation, age of onset of menopause, and duration of menopause (p=0.025, 0.01, 0.049, 0.043, and 0.032 respectively). Conclusion: This study showed postmenopausal women are susceptible to Osteoporosis. J MEDICINE 2022; 23: 132-138